Crop development peculiarities among quinoa foreign varieties (Chenopodium quinoa willd.) in agriclimatic conditions of Crnbez - Evgeniya Mikhailovna Kurenkova; Olga Vladimirovna Kukharenkova; Aleksandra Vasilievna Shitikova (Caspian Journal of Environmental Sciences, 2021)
The modern Russian food market is constantly enriched with new types of products obtained from the crops previously unknown to the domestic consumer. One of the plants of interest in this regard is quinoa, Chenopodium quinoa Willd., a pseudo-grain culture from the Amaranthaceae Juss family of the Chenopodioideae Burnett subfamily. Grain quinoa has a high nutritional value and a unique chemical composition: it has a high protein content (up to 20%), which contains the most important amino acids. It does not contain gluten, and is rich in polyunsaturated oils, vitamins and minerals. The adaptive potential of quinoa allows it to be cultivated in a wide range of agricultural-ecological conditions. It should be noted that quinoa is resistant to abiotic stresses, which is important, taking into account global climate changes, the manifestations of which negatively affect the productivity of traditional agricultural crops.